Implementation of the Padu Satu Public Service Policy at the Center for Plant Variety Protection and Agricultural Licensing Ministry of Agriculture, Jakarta - Rahmat Hadikomara (Jurnal Multidisiplin Sahombu, 2026)
This study examines the implementation of the Padu Satu public service policy at the Center for Plant Variety Protection and Agricultural Licensing within the Ministry of Agriculture in Jakarta. The research aims to analyze how the policy is implemented in practice, identify factors influencing service effectiveness, and explore efforts to improve public satisfaction. A qualitative approach is employed using in depth interviews, observation, and document analysis to capture perceptions and experiences of both service providers and service users. The findings indicate that the Padu Satu policy has contributed to improving service efficiency, transparency, and accessibility through integrated procedures and the use of information technology. However, several challenges remain, including limited socialization, uneven human resource capacity, and constraints in supporting facilities. Effective communication, adequate resources, and commitment of implementers are identified as key determinants of successful policy implementation. Strengthening institutional coordination, enhancing staff competence, and optimizing technological infrastructure are essential to ensure sustainable improvement in public service quality.